Experimental Silica-based Bioceramic Composite Added with Nano-sized Bovine Hydroxyapatite: Synthesis and Characterization - Ferrairo, Brunna Mota (2023)
Purpose: To produce an experimental dense silica-based bioceramic composite added with nano-sized hydroxyapatite (HA) for biomedical application and physicochemical/ microstructurally characterize varying the firing temperature and the amount of binder, polyvinyl butyral (PVB). Methods: Fumed SiO2 and nano-sized HA powder from bovine bone were ball milled aiming the mixture of powders. Groups were divided into HA (3, 5 and 10%), and PVB (1.2 and 2.4 wt.%) addition, and sintering process (1100, 1200 and 1300 °C with a 4 h plateau). The materials were characterized by X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray Spectroscopy analysis (EDX). Results: The group fired at 1200 °C presented potentialized chemical bonds without the degradation of HA at XRD profile, based on its microstructural evolution. FTIR spectra shows the degradation of HA, with an increase of CO2 band and a loss of the calcium-phosphate bands as the temperature increases. The binder concentration showed no chemical changes in the material. 2.4 wt.% of PVB addition resulted in optimized compaction and a lower inclusion of pores or cracks, suggested by SEM images. Conclusion: This study suggests that the match composition of SiO2 matrix with 5% of HA and 2.4 wt.% of PVB, sintered at 1200 °C, exhibit potentially superior properties to biomaterial applications.